From less talk to all talk an analysis of the development of FM programming in the Philippines - Aseron, Marinela M.
"This study traces the beginnings and evolution of FM radio programming in the Philippines from the medium's establishment in the 1960s up to the present. Remarkable changes have taken place through the years in the realm of program formats as well as marketing strategies. These changes have largely been attributed to a number of factors, the most influential of which are technological developments and audience behavior. By virtue of data gathered through verbal accounts of key players in the industry who have witnessed the medium's evolution through the years, combined with the researcher's own first-hand account of its development, the study reveals not only how, when and why these changes occurred, but it also equates these changes with how the Fm raadio industry works as system whose interrelated parts of function as a whole unit, and how it becomes a part of a greater unit called the mass media industry. This study also unravels how such changes point to the political economy of the media industry - the dynamics involved in sustaining the broadcasting business, and how media conglomerates gain control of the supposed "level playing field". It also touches on how the country's cultural identity has been influences by its American colonizers, as evidenced by the workings of the FM radio industry, specifically with regard to programming. The researcher also shares her analyses of such phenomena which she hopes will prove useful to the industry. But more importantly, the researcher regards this study as a pioneering work in the study and documentation of Philippine FM radio history, which she hopes will be helpful to those who plan to conduct future research work related to the topic, and which will offer readers a better understanding of the industry."